Escitalopram-induced sinus bradycardia in coronary heart disease combined with depression: a case report and review of literature - Li, Liu-Cheng; Sun, Wen; Lv, Xiao-Qin; Xu, Yao-Yao; Hu, Ying; Shi, Jia-Na (Frontiers in Cardiovascular Medicine, 2024)
For patients with cardiovascular disease, using the antidepressant escitalopram may lead to unexpected adverse events. Here, a rare repeated sinus bradycardia event due to escitalopram is first reported. In an 82-year-old female patient with cardiac dysfunction using digoxin, tachycardia (average heart rate of 93 beats/min) was demonstrated by electrocardiogram (ECG). She began to take escitalopram and lorazepam due to depression, but sinus bradycardia (93.7% heart rate was <60 beats/min) and sinus arrest were first detected after 3 months. Its proportion decreased to 0.1% after discontinuation of digoxin and escitalopram for 1 day, and the rhythm returned to normal 2 weeks later. After 2 months, escitalopram was prescribed again in combination with quetiapine; then, 17.1% heart rate was <60 beats/min. After escitalopram and quetiapine withdrawal, the ECG showed the heart rhythm had normalized again. No other drug changes were made during these periods. Escitalopram was deemed to be a highly possible cause of sinus bradycardia according to its Naranjo's Algorithm score. Furthermore, literature on escitalopram-mediated cardiovascular adverse events was reviewed and analyzed. Empirically, escitalopram should be discontinued immediately if iatrogenic causes cannot be ruled out. Furthermore, ECG monitoring in escitalopram-related cardiovascular adverse events is highlighted, especially in patients receiving certain drug classes simultaneously (i.e., sinoatrial node inhibitors, antipsychotics).